2015
DOI: 10.1038/gt.2015.49
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated RASSF1A expression suppresses aggressive phenotypes of gastric cancer cells in vitro and in vivo

Abstract: Loss of Ras association domain family protein 1 isoform A (RASSF1A) expression is associated with the development of a variety of human cancers and the expression of carcinoembryonic antigen (CEA) frequently occurs in gastric cancer. This study investigated the effects of RASSF1A expression restoration using a hypoxia-inducible CEA promoter-driven vector on xenograft tumor growth in nude mice and on the in-vitro regulation of gastric cancer cell viability, cell cycle distribution, apoptosis, colony formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In accordance with the above mentioned observations, RASSF1A is expressed in all normal tissues and at a lower level than RASSF1C [24]. Reverting RASSF1A down-regulation in cancer cell lines restores controlled growth and colony formation, as well as decreased cell migration and apoptosis [10,25,26,27,28,29,30].…”
Section: The Tumor Suppressor Rassf1amentioning
confidence: 57%
See 1 more Smart Citation
“…In accordance with the above mentioned observations, RASSF1A is expressed in all normal tissues and at a lower level than RASSF1C [24]. Reverting RASSF1A down-regulation in cancer cell lines restores controlled growth and colony formation, as well as decreased cell migration and apoptosis [10,25,26,27,28,29,30].…”
Section: The Tumor Suppressor Rassf1amentioning
confidence: 57%
“…It is reported that internal or environmental stimuli can promote epigenetic modifications that spread as silent events [85]. For example, RASSF1A m increases during physiological or patho-physiological processes such as aging, hypoxic conditions, senescence, inflammation, and viral infection [30,75,77,91,92,93,94,95]. De novo RASSF1A m associates with different factors and conditions; folate metabolism, DNA polymorphisms, as well as choline-deficient L-amino acid-defined diet in rats [96,97].…”
Section: Mechanisms Of Rassf1a Methylation In Cancer and Agingmentioning
confidence: 99%
“…Oh et al ( 29 ) reported that RASSF1A is required for full activation of macrophage stimulating 1 (Mst1) and enhanced Mst1-mediated apoptosis in vivo . Furthermore, in a previous study, we reported that RASSF1A inhibits SGC-7901 cell invasion under hypoxic conditions, which is associated with matrix metalloproteinase-2 inhibition ( 30 ). Inactivation of RASSF1A may result from multiple mechanisms in tumorigenesis, including transcriptional silencing through promoter hypermethylation, loss of heterozygosity and chromosome deficiency ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…To restore CDX2 expression in colon cancer cells, we constructed an expression vector carrying CDX2 under the control of the hypoxia-inducible hTERT promoter (pLVX-5HRE-hTERTp-CDX2-3FLAG). Targeted genes simultaneously can be dramatically upregulated by 5 copies of a hypoxia response element (HRE) under hypoxic conditions ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%